2014
DOI: 10.1103/physrevb.90.035146
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical unification of hybrid-DFT andDFT+Umethods for the treatment of localized orbitals

Abstract: Hybrid functionals serve as a powerful practical tool in different fields of computational physics and quantum chemistry. On the other hand, their applicability for the case of correlated d and f orbitals is still questionable and needs more considerations. In this article we formulate the on-site occupation dependent exchange correlation energy and effective potential of hybrid functionals for localized states and connect them to the on-site correction term of the DFT + U method. The resultant formula indicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 86 publications
1
53
0
Order By: Relevance
“…With suitably chosen α, the HSE functional can, in many instances, provide a good description of electronic properties ranging from band to Mott-Hubbard insulators as shown in previous work [48,49]. The percentage α of exact-change in hybrid DFT can be semi-quantitatively related to the value of the Hubbard U parameter in DFT+U, with larger values of α (and U) yielding larger optical gaps [48][49][50].…”
Section: Theorymentioning
confidence: 99%
“…With suitably chosen α, the HSE functional can, in many instances, provide a good description of electronic properties ranging from band to Mott-Hubbard insulators as shown in previous work [48,49]. The percentage α of exact-change in hybrid DFT can be semi-quantitatively related to the value of the Hubbard U parameter in DFT+U, with larger values of α (and U) yielding larger optical gaps [48][49][50].…”
Section: Theorymentioning
confidence: 99%
“…Incorrect determination of band gap can, apart from giving wrong estimations of use in electronic materials, also result in the spurious placement of impurity states within the conduction band [124]. A recently developed method, the HSE06+Vw [28][29], intended specifically for this kind of electronic structure and detailed earlier in this thesis has been shown to give improved results through the use of hybrid functionals along with an orbital dependent correction scheme similar to that of LDA+U.…”
Section: Dilute (Tmal)n Alloysmentioning
confidence: 99%
“…The method of hybrid-DFT+Vw was developed by Ivády et al [28][29] and came out of a discovery of similarities between DFT+U and hybrid functionals in terms of corrections to energy and potential. In these papers Ivády et al showed that the correction to exchange energy of the subsystem of correlated orbitals !…”
Section: Hse06+vwmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionals adopted by the condensed matter physics community in the early days of DFT applications to solids were strictly dependent on the electronic density [19,20]; those employed by the chemistry community were instead often defined using linear combinations of Hartree-Fock exchange and density-dependent exchange functionals, which are referred to as hybrid functionals. The latter have also seen many implementations and uses [11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] in condensed matter physics. One successful example of hybrid functionals is that of the optimally tuned rangeseparated hybrid [39], defined using parameters selfconsistently tuned to enforce the validity of Koopman's theorem [40] for molecules.…”
Section: Introductionmentioning
confidence: 99%